Analysis of Activated Carbon from Bituminous Coal as the Primary Battery Cathode Potential Using Fluoric Acid - , Asri Saleh (Archives of Current Research International, 2023)
Activated carbon can generally be made from carbon-containing materials such as coal. The activation in activated carbon synthesis has different activation mechanisms and characteristics. The objective of this study was to analyze the quality and characterization of activated carbon in bituminous coal using a fluoride (HF) activator. The research method was carried out starting from the sample preparation stage, the chemical and physical activation carbonization stage, and the stage of testing the quality of coal-activated carbon. The results showed that each test obtained a moisture content ranging from 0.7% -1.61%. Ash content has a range of values ranging from 17.51% -25.74%, while volatile matter content ranges from 20.96% - 33.97%. The bound carbon content has a range of values ranging from 20.96% -33.97%, iodine numbers range from 3995.4455-4302, 0456 mg/g (all parameters follow SNI 06-3730-1995); and the degree of crystallinity obtained from the concentrations of 3.5 M and 5 M (duplo) has a degree of crystallinity of 26.6218 and 26.6014, respectively. Bituminous coal-activated carbon activated using Hydrogen Flouride (HF) with a temperature of 800 °C has optimal characteristics at a concentration of 5 M with a moisture content of 0.84. The volatile matter content is 18.60, while the iodine absorption capacity is 4.137.0704. The short carbon chain in degrees of crystallization is at an angle of 26.6014 2θ with two diffraction peaks forming a solid crystalline pattern. The surface morphology of activated carbon produces round, neat, and slightly impurities pore with a diameter of 8.81μm.